Quantifying absolute benefit for adjuvant treatment options in renal cell carcinoma: A living interactive systematic review and network meta-analysis. (July 2022) - Riaz, Irbaz Bin; Sipra, Qurat Ul Ain Riaz; Naqvi, Syed Arsalan Ahmed; He, Huan; Siddiqi, Rabbia; Islam, Mahnoor; Asghar, Noureen; Ikram, Waleed; Xu, Wenxin; Liu, Hongfong; Singh, Parminder; Ho, Thai Huu; et al.
Abstract: Objective: To assess comparative effectiveness of adjuvant therapies for renal cell carcinoma and quantify the absolute benefit of adjuvant treatments by clinicopathological risk groups. Methods: This 'living' review was conducted using Living Interactive Evidence (LIvE) synthesis framework. Results: The 'living' results are available on an interactive website. This network meta-analysis, including six RCTs with 7525 participants, showed that pembrolizumab (rank 1) significantly improved disease-free survival and overall survival compared with sunitinib but not when compared to pazopanib, and axitinib. The risk of treatment-related grade 3 or higher adverse events was increased with pembrolizumab as compared to placebo and axitinib but not when compared to sunitinib. The absolute benefit of adjuvant pembrolizumab increases substantially with larger tumor size, nodal positivity and higher Leibovich scores. Conclusion: Current evidence suggests that pembrolizumab delays disease progression compared to sunitinib. A risk-adapted strategy should be used in patients undergoing consideration for treatment with adjuvant pembrolizumab. Highlights: Adjuvant pembrolizumab delays disease progression compared to sunitinib in localized renal cell carcinoma. The absolute benefit of adjuvant pembrolizumab increases with higher nuclear grade, larger tumor size, and nodal positivity. The results of this living, interactive meta-analysis are updated on a linked website as soon as new trials are published.